Theory Development of Genetic Counseling among Patient with Genetic Diseases - Henri Setiawan; Suhanda Suhanda; Elis Roslianti; Andan Firmansyah (Alta Dharma Publisher, 2020)
Genetic Counseling is a communication process undertaken to address the issue of genetic diseases affected in the family. The basic concept of Selfcare is active awareness, while genetic counseling is passive awareness. The nursing theory is based upon the philosophy that all